Temperature effects on bulb growth and inflorescence development of Lachenalia cv. Ronina - Robbertse, P.J. (Petrus Johannes), 1932- (University of Pretoria, 2013)
Thesis (PhD Agric (Horticultural Science))--University of Pretoria, 2007.